KEMAJEMUKAN MASYARAKAT DUSUN SUSURU DESA KERTAJAYA KECAMATAN PANAWANGAN KABUPATEN CIAMIS SEBAGAI MODEL MASYARAKAT PANCASILA - Akhmad Satori (Fakultas Ilmu Sosial dan Ilmu Politik, 2011)
The purpose of this study is to investigate and reveal empirically social, cultural and social life religious, the process of acculturation, social processes (the social system/form of cultural interaction and process systems / customs), the transition process in understanding the diversity of the community, as well as affect the public another model of socio-cultural life and religious communities susuru hamlet. Based on research results seem that Hamlet community Susuru maintain the philosophy of